2021
DOI: 10.48550/arxiv.2111.15537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Model-Free $μ$ Synthesis via Adversarial Reinforcement Learning

Abstract: Motivated by the recent empirical success of policy-based reinforcement learning (RL), there has been a research trend studying the performance of policy-based RL methods on standard control benchmark problems. In this paper, we examine the effectiveness of policy-based RL methods on an important robust control problem, namely µ synthesis. We build a connection between robust adversarial RL and µ synthesis, and develop a model-free version of the wellknown DK-iteration for solving state-feedback µ synthesis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…An important future task is to extend the PGD attack for input-output gain analysis which is crucial for robust control. Recently, the H ∞ input-output gain has been used in robust reinforcement learning [31]- [36]. A general-purpose input-output gain analysis will play a crucial role for the developments of robust DRL methods.…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%
“…An important future task is to extend the PGD attack for input-output gain analysis which is crucial for robust control. Recently, the H ∞ input-output gain has been used in robust reinforcement learning [31]- [36]. A general-purpose input-output gain analysis will play a crucial role for the developments of robust DRL methods.…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%
“…Recently, the H ∞ input-output gain has been used in robust reinforcement learning (Han et al, 2019;Zhang et al, 2020a,b;Donti et al, 2020;Zhang et al, 2021). It has been shown that an efficient input-output gain analysis can be combined with adversarial reinforcement learning (Pinto et al, 2017) to improve the robustness in the linear control setting (Keivan et al, 2021). A general-purpose input-output gain analysis will play a crucial role for the developments of robust DRL in the nonlinear or perception-based setting.…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%
“…In this work, we extend the nonsmooth optimization perspective on µ-synthesis (Apkarian, 2011) to the model-free setting. Notice that the model-free state-feedback µ-synthesis has been previously addressed via combining DK-iteration and a central-path algorithm that adopts robust adversarial reinforcement learning (RARL) as subroutines for finding analytical center in the K step (Keivan et al, 2021). However, such an approach is not directly applicable in the general output-feedback setting.…”
Section: Introductionmentioning
confidence: 99%